Is a blue whale the biggest thing there is? - Wells, Robert E. (London : Watts Books, 1993)
A blue whale is big, in fact it's huge - but is it really the biggest thing there is? To find the answer, set off on an amazing journey of discovery where you will realize that while a whale is big, other things are much, much bigger.
Keywords: Big things